Police investigative interviews and interpreting : context, challenges, and strategies - Mulayim, Sedat (New York, USA : CRC Press, 2015)
"There are a substantial number of publications that cover broader cross-cultural communication issues and role of interpreters in court settings. However, the police interview stage in the criminal justice process has received much less attention. The book is a first attempt, to my knowledge, that has examined in detail the dynamics of how interpreters work in police interviews, especially within the current major investigative interviewing paradigms and it fills a significant gap. This book can be a great resource for professional interpreters and law enforcement officers who work with interpreters in investigative interviews"--
Keywords: Interviewing in law enforcement; Public service interpreting; Translating and interpreting; COMPUTERS / Security / General; LAW / Criminal Law / General; LAW / Forensic Science